Applied Plastics Engineering Handbook : Processing and Materials. - Kutz, Myer (PDL handbook series., 2011)
A practical reference for all plastics engineers who are seeking to answer a question, solve a problem, reduce a cost, improve a design or fabrication process, or even venture into a new market. Applied Plastics Engineering Handbook covers both polymer basics - helpful to bring readers quickly up to speed if they are not familiar with a particular area of plastics processing - and recent developments - enabling practitioners to discover which options best fit their requirements. Each chapter is an authoritative source of practical advice for engineers, providing authoritative guidance from exp.